Contrasting transmission dynamics of co-endemic Plasmodium vivax and P. falciparum: implications for malaria control and elimination - Noviyanti, R; Coutrier, F; Utami, R; Trimarsanto, H; Tirta, Y; Trianty, L; Kusuma, A; Sutanto, I; Kosasih, A; Kusriastuti, R; Hawley, W; Laihad, F; et al. (Public Library of Science, 2015)
BACKGROUND: Outside of Africa, P. falciparum and P. vivax usually coexist. In such co-endemic regions, successful malaria control programs have a greater impact on reducing falciparum malaria, resulting in P. vivax becoming the predominant species of infection. Adding to the challenges of elimination, the dormant liver stage complicates efforts to monitor the impact of ongoing interventions against P. vivax. We investigated molecular approaches to inform the respective transmission dynamics of P. falciparum and P. vivax and how these could help to prioritize public health interventions. METHODOLOGY/PRINCIPAL FINDINGS: Genotype data generated at 8 and 9 microsatellite loci were analysed in 168 P. falciparum and 166 P. vivax isolates, respectively, from four co-endemic sites in Indonesia (Bangka, Kalimantan, Sumba and West Timor). Measures of diversity, linkage disequilibrium (LD) and population structure were used to gauge the transmission dynamics of each species in each setting. Marked differences were observed in the diversity and population structure of P. vivax versus P. falciparum. In Bangka, Kalimantan and Timor, P. falciparum diversity was low, and LD patterns were consistent with unstable, epidemic transmission, amenable to targeted intervention. In contrast, P. vivax diversity was higher and transmission appeared more stable. Population differentiation was lower in P. vivax versus P. falciparum, suggesting that the hypnozoite reservoir might play an important role in sustaining local transmission and facilitating the spread of P. vivax infections in different endemic settings. P. vivax polyclonality varied with local endemicity, demonstrating potential utility in informing on transmission intensity in this species. CONCLUSIONS/SIGNIFICANCE: Molecular approaches can provide important information on malaria transmission that is not readily available from traditional epidemiological measures. Elucidation of the transmission dynamics circulating in a given setting will have a major role in prioritising malaria control strategies, particularly against the relatively neglected non-falciparum species.